Online feedback enhances early consolidation of motor sequence learning and reverses recall deficit from transcranial stimulation of motor cortex. (October 2015) - Wilkinson, Leonora; Steel, Adam; Mooshagian, Eric; Zimmermann, Trelawny; Keisler, Aysha; Lewis, Jeffrey D.; Wassermann, Eric M.
Abstract: Feedback and monetary reward can enhance motor skill learning, suggesting reward system involvement. Continuous theta burst (cTBS) transcranial magnetic stimulation (TMS) of the primary motor area (M1) disrupts processing, reduces excitability and impairs motor learning. To see whether feedback and reward can overcome the learning impairment associated with M1 cTBS, we delivered real or sham stimulation to two groups of participants before they performed a motor sequence learning task with and without feedback. Participants were trained on two intermixed sequences, one occurring 85% of the time (the "probable" sequence) and the other 15% of the time (the "improbable" sequence). We measured sequence learning as the difference in reaction time (RT) and error rate between probable and improbable trials (RT and error difference scores). Participants were also tested for sequence recall with the same indices of learning 60 min after cTBS. Real stimulation impaired initial sequence learning and sequence knowledge recall as measured by error difference scores and impaired sequence knowledge recall as measured by RT difference score. Relative to non-feedback learning, the introduction of feedback during sequence learning improved subsequent sequence knowledge recall indexed by RT difference score, in both real and sham stimulation groups and feedback reversed the RT difference score based sequence knowledge recall impairment from real cTBS that we observed in the non-feedback learning condition. Only the real cTBS group in the non-feedback condition showed no evidence of explicit sequence knowledge when tested at the end of the study. Feedback improves recall of implicit and explicit motor sequence knowledge and can protect sequence knowledge against the effect of M1 inhibition. Adding feedback and monetary reward/punishment to motor skill learning may help overcome retention impairments or accelerate training in clinical and other settings.